Hydatid Cyst of Urinary Tract: 11 Cases at a Single Center - Zargar-Shoshtari, Mohammadali; Shadpour, Pejman; Robat-Moradi, Nader; Moslemi, Mohammadkazem (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} h3 {mso-style-unhide:no; mso-style-qformat:yes; mso-style-link:"Heading 3 Char"; mso-style-next:Normal; margin-top:12.0pt; margin-right:0cm; margin-bottom:3.0pt; margin-left:0cm; mso-pagination:widow-orphan; page-break-after:avoid; mso-outline-level:3; font-size:13.0pt; font-family:"Arial","sans-serif";} span.Heading3Char {mso-style-name:"Heading 3 Char"; mso-style-unhide:no; mso-style-locked:yes; mso-style-link:"Heading 3"; mso-ansi-font-size:13.0pt; mso-bidi-font-size:13.0pt; font-family:"Arial","sans-serif"; mso-ascii-font-family:Arial; mso-hansi-font-family:Arial; mso-bidi-font-family:Arial; font-weight:bold;} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: We retrospectively reviewed clinical records of 11 patients with hydatid cyst of the urinary tract admitted to our institution from 1998 to 2005. Materials and Methods: Hospital and follow-up records of 11 patients with hydatid cyst of the urinary tract were reviewed and data on the patients’ symptoms and signs at presentation, radiological findings, diagnostic tests, pathologic findings, and surgical outcomes were reviewed. Results: The chief complaint was flank pain in 7 patients (63.6%). Hydaturia was not seen in any of our patients. Ten patients had renal involvement and 1 had a retrovesical hydatid cyst. Eosinophilia was detected in 2 of 11 patients who were tested. A positive indirect hemagglutination test was seen in 4 of 7 patients and a positive Casoni test in 1 of 2. Intravenous urography revealed caliceal distortion in 6 patients (54.5%), caliectasis in 3 (27.3%), and nonfunctioning kidney in 2 (18.2%). Ultrasonography showed a complex cyst in all of the patients. Computed tomography demonstrated multivesicular cystic structure in 4 patients (36.4%), complex cyst in 4 (36.4%), and a simple cyst in 3 (27.3%). Definite diagnosis was made only after surgical operation. We performed nephrectomy in 2 patients (18.2%), partial nephrectomy in 2 (18.2%), cystectomy plus marsupialization in 5 (45.4%), and retrovesical surgery in 1 (9.1%). One patient refused surgical treatment. There was no perioperative major complication. Conclusion: Renal hydatidosis is a rare entity and the main challenge is preoperative diagnosis. Radiological and serologic studies, although indicative, cannot confirm the diagnosis, and only pathologic examination after surgical removal can confirm echinococcal infection.